Implementasi Kurikulum Berbasis Aqidah Islam Di STP SMP Khoiru Ummah Medan - Pane, Safira Achmad (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research aims to analyze planning, determine implementation and determine the evaluation of the Islamic Aqidah-based curriculum. To find out this problem, the author uses a qualitative approach method with a descriptive type. Data collection was carried out through interviews, observation and documentation. To analyze the data, the author uses qualitative descriptive analysis, namely processing data and describing situations according to the results of observations, interviews and documentation. The research results show that the curriculum concept is based on Islamic Aqidah, namely the integration of each subject with Islamic Aqidah. Learning is designed by creating curriculum guidelines, academic calendars, determining themes, learning schedules and daily activities. Implementation of learning uses the talqiyyan fikriyyan method. The aim of this Islamic Aqidah-based curriculum is not only to emphasize religion, but it is also hoped that students can master general knowledge without ignoring Islamic values. Meanwhile, the implementation of the Islamic Aqidah-based curriculum is carried out in three stages. The initial stage includes curriculum preparation/planning and learning planning, the second stage contains learning programs, implementation of learning in class, and learning methods. And the final stage includes control and evaluation. Factors that influence curriculum implementation are teachers, parents, students, the environment and the government.